Kemahiran Kepimpinan dalam Kalangan Pengurus Projek Pembinaan Berkenaan Aspek Keselamatan dan Kesihatan Pekerjaan - Mohd Sharif, Shahirah Aida; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
Among the issues that increase the risk of accidents during the implementation of construction projects are the weaknesses in the aspects of leadership and management by project managers and contractors. This study was conducted to examine the challenges faced by project managers in managing construction projects on aspects of occupational safety and health and review improvable measures that can be implemented on leadership skills among project managers regarding aspects of occupational safety and health. The quantitative approach was used in this study by distributing questionnaires to 235 respondents involved, namely project managers working in G7 construction companies around Johor Bahru, Johor. The data obtained were analyzed using Statistical Package for Social Science (SPSS) version 20. The results of the data analysis showed that among the challenges faced by project managers in managing construction projects on safety and health aspects is the attitude of employees who disobey the act/policies displayed, limited time and lack of interest in reading acts/policies as well as limited financial resources. Meanwhile, the improvement measures that can be implemented on leadership skills among project managers regarding aspects of occupational safety and health are project managers need to practice good leadership attitudes such as compliance with rules, improve knowledge and skills in aspects of leadership by attending training and related courses as well project managers make self-assessments through the collection of feedback from employers and colleagues. In conclusion, this study can be used as a reference to the project manager as well as other relevant parties to reduce the risk of accidents and injuries in the construction industry.